MYTHOLOGICAL METAPHORS OF ENGLISH USED TO EXPRESS INSULT - Z. M. Tukhtasinova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article is devoted to the study of the use of English mythological metaphors used in the offensive speech. The dictionary meaning of the words are supported with examples taken from the famous English novels.